(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
In the study region, which is located in Mogod soum, Bulgan Aimag, there is a number of geological and geophysical studies have been conducted due to it is interested in understanding the deep structure of the Khulij hot spring and Mogod fault. Additionally, one of the greatest earthquakes in the XX century in Mongolia occurred in this region. In this study, we report results from newly and more densely measured MTsites in the Mogod region and explain the structure together with the data from past years that have already been measured. The previous one-dimensional depth model was updated with the values of these measurements, and its properties were discussed, which improved the quality of this one-dimensional model compared to the results of our survey in 2022. We also used the SSQ impedance to avoid the effects of near-surface heterogeneities that cause certain distortions in the value of the measurement points.